2017
DOI: 10.1002/aqc.2798
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish in central and southern Ukraine with special focus on populations of indigenous crayfish Astacus pachypus (Rathke, 1837) and their conservation needs

Abstract: 1. The thick-clawed crayfish (Astacus pachypus Rathke, 1837) is the least studied indigenous crayfish species in Europe. Information about its distribution and biology is out of date by more than 15 years.2. This study identified 94 localities with potential occurrence of thick-clawed crayfish in eight southern and central regions of Ukraine, using questionnaire and literature analysis. Based on the information obtained, a field survey was conducted to examine and confirm the current distribution and abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In addition to assessing growth rates, stochastic analysis of the lowland Murray region model showed that increasing variation in the distributions of parameters leads to lower expected minimum population sizes. This highlights that E. armatus populations may be susceptible to highly variable environments (not to be confused with highly variable flows), such as the frequency of disturbance from hypoxic blackwater events, and that ensuring the right kind of environment, such as variable flows and good water quality, may be critical for population persistence (Meyer, Gimpel, & Brandl, ; Policar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to assessing growth rates, stochastic analysis of the lowland Murray region model showed that increasing variation in the distributions of parameters leads to lower expected minimum population sizes. This highlights that E. armatus populations may be susceptible to highly variable environments (not to be confused with highly variable flows), such as the frequency of disturbance from hypoxic blackwater events, and that ensuring the right kind of environment, such as variable flows and good water quality, may be critical for population persistence (Meyer, Gimpel, & Brandl, ; Policar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We accounted for taxonomic synonymy and misidentification by selecting both currently accepted and synonymous genus names, which have been used by different authors in the last decade. In total we retrieved 70 invertebrate genus names belonging to mollusks-gastropods and bivalves (Wesselingh et al, 2019); crustaceans-amphipods, cumaceans, copepods (Monchenko, 2003) and decapods (Policar et al, 2018); mysidae (Audzijonyte et al, 2008); cnidaria and hirudinea (Mordukhay-Boltovskoy, 1960). Finally, we also checked the two genus names of sturgeons (Acipenser and Huso).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…29 of January 19, 2021 on approval of lists of species of animals listed in RDBU and species of animals excluded from RDBU). The new list included an endangered crayfish Astacus pachypus (Bláha et al, 2017;Policar et al, 2018) and a gastropod Clathrocaspia knipowitchii, which were absent from RDBU before. At the same time, species that expanded outside their native range were excluded from the list, for example, Hemimysis anomala and Gmelina pusilla Sars, 1896.…”
Section: Recommendations For Improving the Pontocaspian Legal Landscapementioning
confidence: 99%
“…Another east Ponto‐Caspian crayfish thick‐clawed crayfish Pontastacus pachypus Rathke, 1837, is also known from southern slopes of the eastern Great Caucasus (Azerbaijan) and was suggested to occur in Georgia though it has never been recorded there (Derzhavin 1951) or having disappeared as in most of area of its occurrence in Ukraine (Policar et al . 2018).…”
Section: Introductionmentioning
confidence: 99%